Apolipoprotein B gene mutation related to familial hypercholesterolemia in an Iranian population: With or without hypothyroidism - Golnaz Vaseghi (Wolters Kluwer Medknow Publications, 2021)
Background: Familial hypercholesterolemia (FH) leads to elevated low-density lipoprotein cholesterol (LDL-C) levels in plasma. Mutations of its related gene; apolipoprotein B (APOB) is seen in about two percent of the patient with FH. Thyroid disease is usually part of the exclusion criteria for the detection of FH which alters the lipid profile. We evaluated mutations in the APOB gene in patients with high LDL-C levels. Materials and Methods: Patients aged between 2 and 80 years with at least one LDL-C level of more than 190 mg/dl were selected (120 patients) from Isfahan Laboratories. Blood samples were obtained from all patients. Genomic DNA was extracted. Primer sequences were designed by Oligo 7.60 to amplify the desired 844 bp region of exon 26 of the APOB gene containing R3500Q and R3500W variants associated with FH. Results: Overall, two patients showed a heterozygous form of a common pathogenic variant in exon 26 named c. 10579 C > T (R3500W, cDNA.10707), and one patient was hypothyroidism. We also recognized another nonpathognomonic variant c. 10913G > A (rs1801701, cDNA.11041) in 13 patients, two of them were hypothyroidism. Conclusion: This study for the first time shows the coexistence of APOB mutation in hypothyroidism, which emphasis screening of patients with hypothyroid for FH detection.